HEMATOLOGIC ANALYSIS OF TILAPIA (Oreochromis niloticus) ON ECTOPARASITE INFECTION OF THE FLOATING NET CAGES IN RAWA PENING - Ambarwati, Ninik; Hidayati, Sri; Mujtahidah, Tholibah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2022)
Hematologic analysis of plasma proteins by testing for hemoglobin, erythrocytes, and leukocytes against ectoparasite infection in cages was carried out by taking samples of fish with consumption sizes of 15-20 cm. The aim of this study was to find out the amount of exposure to ectoparasites internally in the body of tilapia based on blood protein hematology test. Analysis of the data used is analysis of variance (ANOVA) with the aim of knowing the effect of sampling and the parameters tested. The results showed that the presence of infection identified normal hemoglobin levels of 7.438 g/dL, erythrocytes were quite low at 1.5605 x1012/L, this is the nutritional factor given to tilapia and leukocytes were still in normal condition, namely 61.985x109/L. The ectoparasites found were Streptococcus sp, Lernea sp, Aeromonas sp, and Trichodina sp. The effect of the value of plasma protein content in blood for hemoglobin and leukocytes is still in normal condition, but erythrocytes are below the normal point so that from internal factors of tilapia disease, hematological blood plasma protein affects tilapia disease, especially on erythrocyte variables that affect fish anemia to mass death. This is in accordance with the situation in the field where tilapia in the KJA (Floating Net Cage) experienced sudden and mass death in a short period of time even though previously routine controls had been carried out by cage cultivators. When fish experience stress, fish blood glucose levels will increase while fish blood plasma total protein levels decrease.